Resource-Efficient Methods to Facilitate the Preservation of a Reservoir's Self-Cleaning Potential - Chelnokov, Vitaliy V.; Matasov, Aleksey V.; Zabolotnaya, Elena; Makarova, Anna S.; Glushko, Andrey N. (KnE Life Sciences, 2022)
The aim of this research was to develop environmental methods for the restoration and rehabilitation of Moscow’s water bodies. A number of methods are recommended. These can help to improve the environmental condition and water quality of water bodiesin Moscow. Keywords: ehabilitation of water body, engineering biology, environmental preservation